Prevalence and diversity of Aphanomyces astaci in cambarid crayfish of Pennsylvania: where native and introduced hosts meet - Petrusek, Adam; Mojžišová, Michaela; Mikešová, Adéla; Piálková, Radka; Lieb, David A (Parasitology, 2025)
The crayfish plague pathogen Aphanomyces astaci (Oomycota: Saprolegniales) is native to North America but expanded with its crayfish hosts to other regions. In most of its invaded range, A. astaci haplotypes are associated with specific American crayfish, probably due to introduction bottlenecks, but haplotype diversity is higher and clear host-specific associations are lacking in its native range. However, little is known about the infection rate and load of this pathogen in North America. We investigated the distribution, prevalence and genetic variation of A. astaci in Pennsylvania (eastern USA), where multiple native and introduced crayfish species (family Cambaridae) occur. We used A. astaci-specific quantitative PCR to screen 533 individuals representing 8 crayfish species (2 Cambarus and 6 Faxonius) from 49 sites. Faxonius limosus, an American species first introduced to Europe and carrier of A. astaci genotype group E, was of particular interest. We confirmed A. astaci infections in 76% of sites in all but 1 host taxon, with the pathogen infection rate and load comparable to established populations of North American crayfish studied in Europe and Japan. Despite the absence of highly infected hosts, we genotyped A. astaci from 14 sites. We only detected 2 mitochondrial haplotypes, but nuclear markers indicated the presence of at least 4 distinct pathogen genotypes, none documented from invaded areas in Europe or Asia. Genotype group E was not detected in F. limosus, possibly due to limited spatial distribution of the original strain. Our results highlight both benefits and limitations of combining multiple pathogen genotyping methods.
Keywords: Animals; Genotype; Prevalence; crayfish plague; native hosts; Aphanomyces; haplogroups; genotyp; Astacoidea; Genetic Variation; prevalence; genotyping; host specificity; Haplotypes; severní raci; zavlečené druhy; Pennsylvania; zvířata; haplotypy; Introduced Species; genetická variace